The Retrohoming of Linear Group II Intron RNAs in Drosophila melanogaster Occurs by Both DNA Ligase 4–Dependent and –Independent Mechanisms - White, Travis B. (Public Library of Science, 2012)
Mobile group II introns are bacterial retrotransposons that are thought to have invaded early eukaryotes and evolved into introns and retroelements in higher organisms. In bacteria, group II introns typically retrohome via full reverse splicing of an excised intron lariat RNA into a DNA site, where it is reverse transcribed by the intron-encoded protein. Recently, we showed that linear group II intron RNAs, which can result from hydrolytic splicing or debranching of lariat RNAs, can retrohome in eukaryotes by performing only the first step of reverse splicing, ligating their 3′ end to the downstream DNA exon. Reverse transcription then yields an intron cDNA, whose free end is linked to the upstream DNA exon by an error-prone process that yields junctions similar to those formed by non-homologous end joining (NHEJ). Here, by using Drosophila melanogaster NHEJ mutants, we show that linear intron RNA retrohoming occurs by major Lig4-dependent and minor Lig4-independent mechanisms, which appear to be related to classical and alternate NHEJ, respectively. The DNA repair polymerase θ plays a crucial role in both pathways. Surprisingly, however, mutations in Ku70, which functions in capping chromosome ends during NHEJ, have only moderate, possibly indirect effects, suggesting that both Lig4 and the alternate end-joining ligase act in some retrohoming events independently of Ku. Another potential Lig4-independent mechanism, reverse transcriptase template switching from the intron RNA to the upstream exon DNA, occurs in vitro, but gives junctions differing from the majority in vivo. Our results show that group II introns can utilize cellular NHEJ enzymes for retromobility in higher organisms, possibly exploiting mechanisms that contribute to retrotransposition and mitigate DNA damage by resident retrotransposons. Additionally, our results reveal novel activities of group II intron reverse transcriptases, with implications for retrohoming mechanisms and potential biotechnological applications.